Case report: Flow changes in routes of collateral circulation in patients with LVO and low NIHSS: a point favor to treat - Santos Neto, Elizeu Pereira dos; de Sousa, Ícaro Araújo; Veras, Arthur de Oliveira; Barros-Araújo, Marx Lima de; Ricarte, Irapuá Ferreira; Pontes-Neto, Octávio Marques (Frontiers in Neurology, 2023)
The effectiveness of endovascular thrombectomy in patients presenting low National 19 Institutes of Health Stroke Scale (NIHSS) scores remains a topic of controversy, and the acquisition 20 of additional evidence is required to refine the selection of candidates who may benefit the most from 21 this therapeutic modality. In this report, we present the case of a 62-year-old individual with left 22 internal carotid occlusion stroke and low NIHSS, in whom compensatory collateral flow from Willis 23 polygon via the anterior communicating artery was noted. The patient subsequently exhibited 24 neurological deterioration and collateral flow failure from Willis polygon, which was an indicative of 25 the need for urgent intervention. The study of collaterals in patients with large vessel occlusion stroke 26 has garnered considerable attention, with research suggesting that individuals with low NIHSS scores 27 and poor collateral profiles may be at a heightened risk of early neurological deterioration. We 28 postulate that such patients may derive significant benefit from endovascular thrombectomy, and 29 posit that an intensive transcranial doppler monitoring protocol could facilitate the identification of 30 suitable candidates for such intervention.